In Silico Design and Molecular Docking Studies of Carbapenem Analogues Targeting Acinetobacter baumannii PBP1A Receptor - Twana Salih; Hawzhin A. Salih (College of Pharmacy / Mustansiriyah University, 2020)
Carbapenems are considered as the most effective antibiotic against Acinetobacter baumannii infections, as the pathogen has a resistance to the most of the other beta-lactam antibiotics; however, recent studies proved that this pathogen has developed resistance to carbapenems, as well. Therefore, development of novel therapeutics targeting A. baumannii resistant strains is an urgent global requirement. One of the causes responsible for this bacterial resistance against beta-lactam antibiotics is the decreased strength of interactions between A. baumannii Penicillin-Binding Proteins 1A (PBP1A) and carbapenems. Therefore, the aim of this study is to design a novel analogue of imipenem with significantly higher binding affinity and improved drug-likeness properties to overcome resistance of the pathogen and optimize bioavailability, respectively. De novo drug design was performed using virtual screening to predict the ligand(s) with the highest binding affinity. The two-dimensional and three-dimensional structure of the designed molecules were sketched using Chemdraw professional and MarvinSketch, respectively. After separating the targeted protein from A. baumannii PBP1A-imipenem complex structure (3UDX) and retaining a monomer (chain A) from a dimer of the protein structure using Text Editor (ConTEXT v0.98.6), docking was achieved using virtual screening AutoDock Vina program. Finally, drug-likeness properties were assessed. The results could find the selected compounds with significantly higher binding affinity and improved physicochemical properties compared with imipenem.